2010
DOI: 10.1103/physreva.82.065401
|View full text |Cite
|
Sign up to set email alerts
|

Low-energy fine-structure resonances in photoionization of O ii

Abstract: Resonant features in low-energy photoionization cross sections are reported in coupled-channel calculations for O II including relativistic fine structure. The calculations reveal extensive near-threshold resonant structures in the small energy region between the fine structure levels of the ground state 2p 2 ( 3 P 0,1,2 ) of the residual ion O III. Although the resonances have not yet been observed, they are similar to other experimentally observed features. They are expected to significantly enhance the very… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…A much larger set of correlation configurations is included for configuration interaction with the spectroscopic terms using the atomic structure code SU-PERSTRUCTURE (Eissner et al 1974, Nahar et al 2003): [1s 2 ]2p 4 , 2s 2 2p3p, 2s 2 2p3d, 2s 2 2p4s, 2s 2 2p4p, 2s2p 2 3s, 2s2p 2 3p, 2s2p 2 3d, 2s 2 3s 2 , 2s 2 3p 2 , 2s 2 3d 2 , 2s 2 4s 2 , 2s 2 4p 2 , 2s 2 3s3p, 2s 2 3s4s, 2s 2 3p3d, 2p 3 3s, 2p 3 3p, 2p 3 3d. We note here that the crucial fine structure separations between the ground state 3 P0,1.2 levels reproduced theoretically agree with experimentally measured values to ∼3% (Nahar et al 2011, see Pradhan and Nahar (2011) for a general description of atomic processes and calculations). The observed energies were substituted for theoretical ones in order to reproduce the threshold energies more accurately.…”
Section: Wavefunction Representation and Calculationssupporting
confidence: 88%
See 2 more Smart Citations
“…A much larger set of correlation configurations is included for configuration interaction with the spectroscopic terms using the atomic structure code SU-PERSTRUCTURE (Eissner et al 1974, Nahar et al 2003): [1s 2 ]2p 4 , 2s 2 2p3p, 2s 2 2p3d, 2s 2 2p4s, 2s 2 2p4p, 2s2p 2 3s, 2s2p 2 3p, 2s2p 2 3d, 2s 2 3s 2 , 2s 2 3p 2 , 2s 2 3d 2 , 2s 2 4s 2 , 2s 2 4p 2 , 2s 2 3s3p, 2s 2 3s4s, 2s 2 3p3d, 2p 3 3s, 2p 3 3p, 2p 3 3d. We note here that the crucial fine structure separations between the ground state 3 P0,1.2 levels reproduced theoretically agree with experimentally measured values to ∼3% (Nahar et al 2011, see Pradhan and Nahar (2011) for a general description of atomic processes and calculations). The observed energies were substituted for theoretical ones in order to reproduce the threshold energies more accurately.…”
Section: Wavefunction Representation and Calculationssupporting
confidence: 88%
“…( 2) representes the one-body terms of the Breit interaction. In addition, another version of BPRM codes including the two-body terms of the Breit-interaction (Nahar et al 2011; W. Eissner and G. X. Chen, in preparation) has been developed, and is employed in the present work.…”
Section: Relativistic Fine Structurementioning
confidence: 99%
See 1 more Smart Citation
“…García-Rojas et al (2007b) suggest that the problem stems from the presence of temperature fluctuations, whereas Liu et al (2000) argue that it comes from hydrogen deficient clumps in the nebula. Recently, Nahar et al (2010) have suggested that the abundance discrepancy problem is caused by an underestimate of the low-temperature (10 2 −10 4 K) dielectronic recombination rates. Based on theoretical calculations they argue that resonant features in the low-energy photoionization cross section of O ii must be included.…”
Section: O/h Abundance Ratiomentioning
confidence: 99%
“…(3) representes the one-body terms of the Breit interaction. Another version of "full" BPRM codes has been developed including the two-body terms, but those are only of importance in forbidden (E2, M1, M2) transitions where two-electrons correlations may play an important role [25]. In contrast, plasma opacities in toto are determined by strong E1 (dipole allowed and intercombination) considered in this work.…”
Section: Theorymentioning
confidence: 99%